Middlebrow Modernism : Eleanor Dark's Interwar Fiction. - Cooper, Melinda J. (Sydney studies in Australian literature., 2022)
Eleanor Dark (1901-1985) is one of Australia's most significant novelists, and her work is currently enjoying a revival of critical interest. This book will provide the first sole-authored critical survey of Dark's fiction to be published in over four decades. Focusing on Dark's ten novels - Slow Dawning (1932), Prelude to Christopher (1934), Return to Coolami (1936), Sun Across the Sky (1937), Waterway (1938), The Timeless Land (1941), The Little Company (1945), Storm of Time (1948), No Barrier (1953) and Lantana Lane (1959) - as well as other writings that have tended to be overlooked, such as her juvenilia, magazine fiction, and unpublished manuscripts, this book will position Dark's work as important for the study of Australian literature, global modernism and world literature.